The Impact of Personal Experience on Behavior: Evidence from Video-Rental Fines - Haselhuhn, Michael P.; Pope, Devin G.; Schweitzer, Maurice E.; Fishman, Peter (Management Science, 2012)
Personal experience matters. In a field setting with longitudinal data, we disentangle the effects of learning new information from the effects of personal experience. We demonstrate that experience with a fine, controlling for the effect of learning new information, significantly boosts future compliance. We also show that experience with a large fine boosts compliance more than experience with a small fine, but that the influence of experience with both large and small fines decays sharply over time. This paper was accepted by Brad Barber, Teck Ho, and Terrance Odean, special issue editors.